Ferramenta computacional web baseada em algoritmos genéticos para roteamento de veículos - Santos, Renato Alessandro Rocha (2017)
Over the last decades the Vehicle Routing Problem (VRP) has been subject of research of several authors, mainly because of difficulties found in its optimization as well as its application in real-world situations. In the scientific literature there are several proposed solutions for the PRV using different optimization techniques. However, such solutions are rarely transformed into software tools that can be used by end users, for example, micro enterprises. Thus, the focus of the present work was to develop a Web computational tool for vehicle routing, called “SGRV  Sistema de Gestão de Roteamento de Veículos”, which uses Google Maps features and aims to meet the needs of micro enterprises. Therefore, initially it was conducted a literature search about solution methods for VRP, to support the choice of strategy based on genetic algorithms employed in SGRV. Then, a new bibliographic research was made with the purpose of finding free softwares for the VRP solution, which were object of analysis to mark out the development of the SGRV. For the development of this research was used the methodology Design Science Research. A qualitative evaluation of the SGRV was carried out by four microenterprises from different branches, that used the tool for a certain period and, in the end, answered six questions opened from semi-structured interviews. The experiences of these microenterprises were transcribed and the data obtained reveal the effectiveness of the SGRV in the management of its tasks related to the orders and deliveries of products.